Jasa Ekosistem dalam Isu-Isu Kritis Lingkungan - Zairin Zairn; Warsa Sugandi Karman; Supriyono Supriyono; Muhammad Alfi; Mirna Yunita (Universitas Prof. Dr. Hazairin, S.H, 2022)
The world is currently experiencing a very powerful climate shift. Global temperature is believed to continue to increase. This trend will continue if not controlled. Concern for the environment has become a global issue due to several factors. first, environmental problems always have global effects, for example, problems involving CFCs (Chlorofluorocarbons) which have an effect on global warming and increase the types and quality of diseases due to the hole in the ozone layer felt by the world's population. secondly, environmental issues also concern the exploitation of global resources such as the oceans and the atmosphere. third, environmental problems are always transnational in nature so environmental damage in one country can impact other countries, for example, the forest fires that occurred in Kalimantan could hamper flights to Singapore. This can make the sovereignty of a country meaningless when an ecosystem is disturbed. The impact it causes depends on how large an ecosystem is damaged. The wider an ecosystem is damaged, the wider/larger the impact will be. fourth, there are many exploitation activities that cause environmental degradation on a local or national scale which can cause global problems, such as excessive logging, water pollution, and other problems.